Implementation of Environmental-friendly Food Packaging in Malaysia: Current Reality of Kelantanese Hawkers - Nur Dalila, Mat Yusoff; Hamrila, Abdul Latif; Norizan, Jaafar; Ikhwan, Aziz (Roman Science Publications Inc, 2021)
Numerous promotions and campaigns have been launched by the Malaysian government and non-government organizations to raise the awareness of environmental-friendly food packaging (EFFP). However, the implementation of EFFP among food sellers or retailers is still low. Therefore, this study aimed to focus on the current reality of the usage of EFFP among Malaysian food hawkers in Kelantan. A total of 100 hawkers from night markets in the state were sampled and interviewed. It was found that only 25% hawkers used EFFP. Data were analyzed by using frequency and crosstab to analyze their views on perceived benefits, perceived risks and resource conditions. It can be concluded from the findings of the study that more efforts should be made in order to raise the awareness level of EFFP so that its use can be spread to food hawkers and other food handlers and retailers.